Blockade of sigma 1 receptors alleviates sensory signs of diabetic neuropathy in rats. (24th June 2016) - Paniagua, N.; Girón, R.; Goicoechea, C.; López‐Miranda, V.; Vela, J.M.; Merlos, M.; Martín Fontelles, M.I.
Abstract: Background: E‐52862 (S1RA, 4‐[2‐[[5‐methyl‐1‐(2‐naphthalenyl)‐1H‐pyrazol‐3‐yl]oxy]ethyl]‐morpholine), a novel selective sigma 1 receptor (σ1R) antagonist, has demonstrated efficacy in nociceptive and neuropathic pain models. Our aim was to test if σ1R blockade with E‐52862 may modify the signs of neuropathy in Zucker diabetic fatty (ZDF) rats, a type 2 diabetes model. Methods: Mechanical and thermal response thresholds were tested on 7‐, 13‐, 14‐ and 15‐week‐old ZDF rats treated with saline or with E‐52862 acutely administered on week 13, followed by sub‐chronic administration (14 days). Axonal peripheral activity (skin–saphenous nerve preparation) and isolated aorta or mesenteric bed reactivity were analysed in 15‐week‐old ZDF rats treated with saline or E‐52862 and in LEAN rats. Results: Zucker diabetic fatty rats showed significantly decreased thermal withdrawal latency and threshold to mechanical stimulation on week 13 compared to week 7 (prediabetes) and with LEAN animals; single‐dose and sub‐chronic E‐52862 administration restored both parameters to those recorded on week 7. Regarding axonal peripheral activity, E‐52862 treatment increased the mean mechanical threshold (77.3 ± 21 mN vs. 19.6 ± 1.5 mN, saline group) and reduced the response evoked by mechanical increasing stimulation (86.4 ± 36.5 vs. 352.8 ± 41.4 spikes) or by repeated mechanical supra‐threshold steps (39.4 ± 1.4 vs. 83.5 ± 0.9). E‐52862 treatment also restored contractile response to phenylephrine in aorta and mesenteric bed. Conclusions: E‐52862 administration reverses neuropathic (behavioural and electrophysiological) and vascular signs in the ZDF rat. Significance: Blockade of σ1R avoids the development of diabetic neuropathy in rats, and may represent a potentially useful therapeutic approach to peripheral neuropathies in diabetic patients. What does this study add?: This study presents evidences for the potential usefulness of sigma receptor blockade on diabetic neuropathy in rats. The methodology includes behavioural evidences, electrophysiological data and vascular‐isolated models.